2013
DOI: 10.1517/14740338.2013.770471
|View full text |Cite
|
Sign up to set email alerts
|

Thein vitroandin vivoeffects of nicotine on bone, bone cells and fracture repair

Abstract: The review suggests that nicotine has effects on osteoneogenesis, osseointegration and steady-state skeletal bone in animal in vivo models, as well as effects on all 'bone cells', via several mechanisms in both animal and human cell in vitro studies. The effect of nicotine is dose-dependent, with higher concentrations having predominantly negative effects, whereas at low concentrations a stimulatory effect is seen. Stimulatory effects on certain cells may indicate a possible, limited therapeutic role; advice r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 102 publications
1
34
0
2
Order By: Relevance
“…Such mechanisms include direct and indirect cellular effects on bone cells involving all skeletal sites. 21 …”
Section: Pathophysiological Mechanisms Of Tobacco Smoking On Developmmentioning
confidence: 99%
See 1 more Smart Citation
“…Such mechanisms include direct and indirect cellular effects on bone cells involving all skeletal sites. 21 …”
Section: Pathophysiological Mechanisms Of Tobacco Smoking On Developmmentioning
confidence: 99%
“…21 The actions may be receptor-mediated via a nicotinic acetylcholine receptor. Low levels of nicotine upregulate osteocalcin, type I collagen and alkaline phosphatase gene expression.…”
Section: Direct Effects On Bone Cellsmentioning
confidence: 99%
“…In vivo studies have demonstrated that tobacco smoking is a major risk factor for osteoporosis [1,2]. Nicotine, one of the main compounds in cigarette, influences the biological activity, proliferation, and differentiation of osteoblasts [3][4][5]. In addition, nicotine can also suppress the osteoblast differentiation from human mesenchymal stem cell (MSC) [6].…”
Section: Introductionmentioning
confidence: 99%
“…These differences can be explained by the interaction between growth/hormone factors and rougher surface topography that favor cellular differentiation and mineralization. This beneficial effect of rough surfaces in osseointegration has been confirmed by experimental and clinical studies 14,20,22 . In addition, low concentrations of nicotine showed a stimulatory effect on cell replication, especially at low concentrations (0.025 µM), it had a significant stimulatory effect on fibroblast proliferation 22 as well as in human osteoblast-like cells 23 , which could explain the higher torque necessary to remove the implants in nicotine than in control group found in the present study.…”
Section: ■ Discussionmentioning
confidence: 64%